The efficiency of the seismic isolating sliding belt under the impact of the most unfavourable earthquake accelerograms - O. V. Mkrtychev; S. R. Mingazova (Vestnik MGSU)
Introduction. Research was carried out on the performance of monolithic reinforced concrete buildings of varying heights with and without a seismic isolating sliding belt when subjected to the most unfavourable earthquake accelerograms. The objective of the study is to assess the effectiveness of seismic isolation in the form of a sliding belt at the foundation level under the action of the most unfavourable earthquake accelerograms using a direct nonlinear dynamic method.Materials and methods. The study employed a direct dynamic method based on an explicit integration scheme of the equation of motion (the central difference method). To determine the most unfavourable earthquake accelerograms, a method was used that accounted for all the most significant natural frequencies of the building under consideration.Results. Based on the calculations conducted, relative displacements and stress intensities for the building as a whole and in detail for the most loaded floor were determined. The analysis of the obtained results showed a significant reduction in shear displacements and stress intensities with the use of seismic isolation in the form of a sliding belt at the foundation level.Conclusions. When selecting the type of seismic isolation, its cost, as well as the labour intensity of manufacturing and installation, must be considered. It is necessary for the seismic isolation systems used to be available for mass construction, less complex, and maximally effective. Proven materials and technologies for the installation of these systems, which do not require specific skills and qualifications, should be used. Seismic isolation should provide comprehensive protection against the most likely seismic impacts. Conducted research shows that the seismic isolating sliding belt meets the above requirements. Unlike widely used rubber-metallic and pendulum sliding bearings, seismic isolation in the form of a sliding belt at the foundation level does not require factory manufacturing and can be implemented directly at the construction site.